1982
DOI: 10.1063/1.1137191
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the spin polarization of an optically pumped ensemble of He (23S) atoms

Abstract: A technique is described that enables simple, direct determination of the spin polarization of an optically pumped ensemble of He (23S) atoms. The polarization is obtained from measurements of the attenuation of the circularly polarized output of a color-center laser tuned to the 1.08 μm He (23S1→23P0) transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…2 3 P 0 transition (D 0 line). 2) On the other hand, Wallace et al demonstrated that P He à is obtained by similar measurements for three separate transitions of He à 2 3 S 1 to 2 3 P 0 (D 0 line), 2 3 P 1 (D 1 line), and 2 3 P 2 (D 2 line) (Fig. 1).…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…2 3 P 0 transition (D 0 line). 2) On the other hand, Wallace et al demonstrated that P He à is obtained by similar measurements for three separate transitions of He à 2 3 S 1 to 2 3 P 0 (D 0 line), 2 3 P 1 (D 1 line), and 2 3 P 2 (D 2 line) (Fig. 1).…”
mentioning
confidence: 79%
“…In this configuration, rhcp, lhcp, and linearly polarized (lp) probe beams can be absorbed only by He à with m J ¼ À1, þ1, and 0, respectively. Thus, the intensity I of the transmitted probe beam is 2) IðrhcpÞ ¼ I 0 ðrhcpÞ expðÀn À LÞ;…”
mentioning
confidence: 99%